Targeting BCL-2 proteins in pediatric cancer: Dual inhibition of BCL-XL and MCL-1 leads to rapid induction of intrinsic apoptosis. (10th July 2020) - Kehr, Sarah; Haydn, Tinka; Bierbrauer, Annika; Irmer, Barnabas; Vogler, Meike; Fulda, Simone
Abstract: With the development of potent and selective inhibitors of MCL-1 (S63845) and BCL-XL (A-1331852) novel cancer treatment options have emerged. BCL-2 family proteins are important regulators of apoptosis in pediatric solid tumors. In the current study, we discover that rhabdomyosarcoma, Ewing sarcoma, osteosarcoma and neuroblastoma cell lines are co-dependent on BCL-XL and MCL-1 for survival. A-1331852/S63845 co-treatment, but not combinations of either inhibitor with ABT-199, synergistically induces rapid intrinsic apoptosis in vitro and demonstrates efficiency in an in vivo embryonic chicken model of rhabdomyosarcoma. Interestingly, A-1331852/S63845-induced apoptosis is BAX/BAK-dependent and mediated by displacement of BAK from BCL-XL and MCL-1, respectively. Moreover, BAK interacts with BAX to build a pore-forming complex in the outer mitochondrial membrane, leading to loss of mitochondrial outer membrane potential and caspase activation. Furthermore, in RD cells A-1331852/S63845 co-treatment disrupts BIM and NOXA in their interactions with BCL-XL and MCL-1, respectively, thereby contributing to apoptosis. Altogether, this study is the first to demonstrate the potency of A-1331852/S63845 in pediatric solid tumor cells and to describe the molecular mechanisms of A-1331852/S63845 co-treatment underlining the potential of BCL-XL and MCL-1 inhibition as treatment regime. Graphical abstract: Image 1 Highlights: Co-inhibition of MCL-1 and BCL-XL induces synergistic apoptosis in pediatric cancer. S63845/A-1331852 co-treatment effectively induces apoptosis in vitro and in vivo . S63845/A-1331852 induces rapid apoptosis by releasing BAK from MCL-1 and BCL-XL .